PERAN WWF DALAM PENGELOLAAN TAMAN NASIONAL KOMODO DI INDONESIA TAHUN 2017-2019 - Nurhayati "; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study describes the role of WWF as an international organization in the management of Komodo National Park which is experiencing various problems due to the lack of public awareness of conservation. WWF is an international organization dealing with environmental conservation, research and restoration issues. Since the existence of the WWF organization, WWF has supported the Komodo National Park Office for the management of its area by making various efforts to achieve Komodo dragon conservation in Indonesia. This research uses a pluralism perspective that supports international organization theory and the level of group analysis as actors. This research uses qualitative methods and literature study as a source of information. The author collects data related to the problem under study such as from books, journals, website, WWF annual activity reports to analyze the management problems of Komodo National Park in Indonesia. The results show that WWF as an international organization only acts an actor in the management of Komodo National Park in Indonesia. Because, WWF only contributes in overcoming various problems that occur in Komodo National Park. WWF’s role as an actor can be seen from the work programs carried out by WWF in Komodo National Park, such as WWF collaborating with the Komodo Survival Programme in monitoring the Komodo dragon population and their habitat, preparing a tourism master plan and managing waste.WWF also collaborates with the Komodo National Park Office in holding FGDs and WWF does fundraising independently. Keywords: Komodo National Park, Management, Role, and WWF